The Role of the Mupunjung Custom in Fostering Social Cohesion in the Village of Rancah: Rituals, Social Capital, and Community Integration: Rituals, Social Capital, and Community Integration - Muhamad Rizky Aditya; Rida Permatasari (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2026)
This study investigates the role of the Mupunjung tradition in fostering social cohesion within the community of Rancah Village, West Java, Indonesia. In the context of increasing social fragmentation driven by modernization, mobility, and digitalization, the study explores how local ritual practices continue to function as mechanisms of social integration and cultural continuity. A qualitative case study approach was employed through in-depth interviews with traditional leaders, community members, participant observation, and document analysis. Data were analyzed using thematic coding and triangulation. The findings reveal that Mupunjung functions not merely as a cultural ritual but as a social institution that strengthens collective solidarity, reinforces trust-based social networks, transmits cultural values, and reproduces collective identity. The ritual provides a shared symbolic space where cooperation, reciprocity, and communal responsibility are continuously enacted. However, the study also identifies challenges related to declining youth participation and the persistence of symbolic authority within traditional structures. The findings demonstrate that ritual operates simultaneously as a mechanism of social cohesion, social capital formation, cultural reproduction, and symbolic power, highlighting the continuing relevance of local traditions in strengthening community resilience amid contemporary social change.